A new species (Begonia iarae) of Begoniaceae from Ilhabela, São Paulo, Brazil - Miranda, Marcelo Dias (Phytotaxa, 2025)
A new species of Begonia (Begoniaceae), from Brazil is described and illustrated with field photographs. Begonia iarae belongs to Begonia sect. Pritzelia, and it is endemic to the Atlantic Forest of São Sebastião island, occurring in montane cloud forest of Ilhabela municipality. A comparison with related species and a preliminary IUCN Red List assessment of Critically Endangered is provided for the species.